In the shadow of empire Israel and Judah in the long Sixth century BCE - Barmash, Pamela 1966-; Hamilton, Mark W. 1964- (Atlanta SBL Press, Society of Biblical Literature, 2021)
Cover -- Contents -- Acknowledgments -- Abbreviations -- Figure Credits -- Introduction -- Success and Failure, Resistance and Submission -- The Art of Control -- Controlling the Narrative -- Bury Me with My Fathers -- The Exiles of Empires in Prophetic Images of Restoration (and Micah 4:8-5:! [ET 5:2]) -- "Empire" as a Political Category and Reflections on It in Centers and Peripheries -- Far Side of the Long Sixth Century -- Remembering the Future -- Bibliography -- Contributors -- Ancient Sources Index -- Modern Authors Index -- Subject Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung